АНАЛІЗ ТРАКТУВАННЯ ПОНЯТТЯ “ПРОФЕСІЙНИЙ ІМІДЖ” У НАУКОВІЙ ЛІТЕРАТУРІ (Педагогіка вищої та середньої школи, 2006)
The article is devoted to different approaches to the category “image ”, its main characteristics, types. The own notion of the term “the professional image” is considered.